2021
DOI: 10.1525/sod.2021.7.2.202
|View full text |Cite
|
Sign up to set email alerts
|

The Exclusionary Power of Microfinance

Abstract: In recent years, international banks, investment agencies, and development institutions have created new markets for capital accumulation by rapidly expanding the commercial microfinance industry in the global South. In Cambodia, which has one of the largest microfinance industries in the world, the typical loan amount now exceeds the average annual household income and requires land-based collateral. Cambodian borrowers are increasingly over-indebted, compelling families to reduce their food consumption, take… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(36 citation statements)
references
References 42 publications
0
36
0
Order By: Relevance
“…The reduced availability of wild food connected to forest enclosures facilitates dependence on credit from local grocery stores and micro-finance institutions (MFIs) as the commons no longer provide a reliable food security safety net and market bought food is expensive (Bateman, 2012;Green and Bylander, 2020). While there have not, as yet, been any large-scale studies on the gender dimensions of indebtedness and land loss in rural Cambodia, it has been observed that more than 70% of micro loans are provided to women and many of these are given for the purposes of buying food and medicines or for servicing repayments on earlier loans (Green and Bylander, 2020). Our interviewees discussed indebtedness arising from and leading to food insecurity and the heavy mental load involved in managing household finances in a context where multiple loan repayments must be navigated.…”
Section: Increasing Indebtedness As a Results Of Enclosurementioning
confidence: 99%
“…The reduced availability of wild food connected to forest enclosures facilitates dependence on credit from local grocery stores and micro-finance institutions (MFIs) as the commons no longer provide a reliable food security safety net and market bought food is expensive (Bateman, 2012;Green and Bylander, 2020). While there have not, as yet, been any large-scale studies on the gender dimensions of indebtedness and land loss in rural Cambodia, it has been observed that more than 70% of micro loans are provided to women and many of these are given for the purposes of buying food and medicines or for servicing repayments on earlier loans (Green and Bylander, 2020). Our interviewees discussed indebtedness arising from and leading to food insecurity and the heavy mental load involved in managing household finances in a context where multiple loan repayments must be navigated.…”
Section: Increasing Indebtedness As a Results Of Enclosurementioning
confidence: 99%
“…I have previously published about the relationship between microfinance and Cambodia's agrarian transformation. This research was based on long-term ethnographic research within a farming community and a local microfinance institution (Green 2019(Green , 2020a(Green , 2020bGreen and Bylander, 2021;Estes 2019, 2022). More recently, I have conducted interviews with national regulators, financial executives, investors, and civil society organizations involved with microfinance.…”
Section: Methodsmentioning
confidence: 99%
“…Another issue raised by farm mortgages relates to land dispossession. Political ecologists and development geographers, building on agrarian Marxist theories of rural differentiation, have argued that the rise of interlocked land and credit markets has driven new waves of dispossession in the global south (Casolo and Doshi, 2013; Green and Bylander, 2021; Hall, 2004; Hall et al, 2011; Li, 2014a; Taylor, 2011). According to this literature, debt is a mechanism of alienating land from rural producers once capitalist market imperatives and property relations have been established in the countryside.…”
Section: Geographic Approaches To Agrarian Financementioning
confidence: 99%
“…They are also shaped by powers of legitimation and regulation. Similar to the morality of microfinance, debt-driven dispossession is frequently legitimized by shifting responsibility of default onto borrowers and coercing land sales through public shaming practices (Green and Bylander, 2021). Moreover, states have variously intervened in land markets to regulate debt-driven land sales in response to agrarian discontent and revolt (Hall et al, 2011).…”
Section: Geographic Approaches To Agrarian Financementioning
confidence: 99%
See 1 more Smart Citation